2004
DOI: 10.1111/j.1365-2923.2004.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medical students' ethnicity on their attitudes towards consultation skills and final year examination performance

Abstract: The only significant difference regarding attitudes to consultation skills was that non-Western born students placed significantly greater importance on communication skills and the traditional diagnostic method postattachment than Western born students. No significant differences were found in attitudes preattachment. There were significant differences in performance, with students of ethnic background performing consistently poorer in all the final year assessment parameters analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 17 publications
(19 reference statements)
5
46
1
Order By: Relevance
“…As for country of birth, this is a confirmation of the earlier reports of Laidlaw et al (2006) and Liddell and Koritsas (2004) that nonnative speakers score lower on communication skills. In our findings, they do so on both sub-scales.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As for country of birth, this is a confirmation of the earlier reports of Laidlaw et al (2006) and Liddell and Koritsas (2004) that nonnative speakers score lower on communication skills. In our findings, they do so on both sub-scales.…”
Section: Discussionsupporting
confidence: 89%
“…Because there are indications that empathy is not easily trained, this is valuable information for educators (Stepien & Baernstein 2006;Brunero et al 2010). Three of the four MG items with the lowest scores (even after undergoing doctor-patient communication skills training) are part of the patient-oriented subscale (Clarification of the reason for encounter, Summarizing and Dealing with emotions) and it might, therefore, not be easy to improve these skills (Kramer et al 2004;Liddell & Koritsas 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was related to the fact that there is a current emphasis on patient centered care and women are more naturally inclined to render empathetic care than men 4, and empathetic care may present a considerable difficulty for students from more paternalistic cultures. [5][6][7][8] Yates and James 9 in a study to identify potential predictors of undergraduate students who struggle during their medical training found the male gender to be a significant factor, though less so than other identified factors and suggested that males might do less well on the Nottingham course, a fact they intend to further study. Females have been noticed from literature review to perform better than males in their medical training.…”
Section: Analysis Of Final Year Medical Students' Examination In Surgerymentioning
confidence: 99%
“…For example, ME and male students have been found to score lower in final clinical and written examinations (Liddell & Koritas, 2004;Koenig et al, 1998;Lumb & Vail, 2004;Xu et al, 1993) be less likely to achieve honours in a medical degree (James & Chilvers, 2001), and be more likely to fail final examinations compared to their female and White counterparts (Dillner, 1995;McManus et al, 1996;Wass et al, 2003). In Australia, students of Aboriginal and Torres Island origin were more likely to be rated "unsatisfactory" in first year medical examinations compared to students of European origin (Kay-Lambkin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%